Association between solid cooking fuels exposure and metabolic syndrome: Evidence from China - Jiaming Xue; Shuai Chen; Yicheng Jiang; Qi Liu; Yu Wang; Yuwen Jiao; Yuancheng Shao; Jie Zhao; Yan Zhou; Dongmei Wang; Liming Tang (Ecotoxicology and Environmental Safety, 2025)
Epidemiological evidence connecting cooking fuel use to metabolic syndrome (MetS) is lacking. Solid cooking fuel usage and MetS prevalence were prospectively investigated in this study. We included participants in 2011 and 2015 from the China Health and Retirement Longitudinal Study (CHARLS) data. Through cross-sectional and longitudinal studies, we found that the use of solid fuels reduced the risk of MetS in participants compared with clean fuels (cross-sectional study: 2011: Odds ratio (OR): 0.819, 95 %confidence interval (CI): 0.747–0.897, P < 0.001; 2015: OR: 0.766, 95 %CI: 0.708–0.851, P < 0.001; longitudinal study: OR: 0.736, 95 %CI: 0.652–0.831, P < 0.001).This impact ceases to exist whenever a switch in fuel type occurs (Non persistent clean: OR: 0.937, 95 %CI: 0.837–1.050, P = 0.262; Persistent solid: OR: 0.767, 95 %CI: 0.691–0.853, P < 0.001). Moreover, we found that biomass (crop residue and wood burning) combustion reduced the prevalence of MetS (OR: 0.653, 95 %CI: 0.573–0.743, P < 0.001), while coal had no effect on the prevalence of MetS (OR: 1.092, 95 %CI: 0.907–1.315, P = 0.352). Based on mediation analysis, triglyceride (TG) and high-density lipoprotein cholesterol (HDL-C) cholesterol mediated 61.3 % and 39.8 % of the reduction in MetS prevalence observed with solid fuel. In summary, our research showed that household solid cooking fuels were associated with less MetS risk. Among them, biomass combustion may play an important role.